Cross-sectional Study of Workers Employed at a Copper Smelter—Effects of Long-term Exposures to Copper on Lung Function and Chronic Inflammation. Issue 9 (28th September 2022) - Haase, Lisa-Marie; Birk, Thomas; Poland, Craig A.; Holz, Olaf; Müller, Meike; Bachand, Annette M.; Mundt, Kenneth A.
Abstract : The present cross-sectional study investigates whether biological relevant differences in lung function and inflammatory biomarkers exist between workers of a German copper plant and an internal comparison group. It complements a previously published historical health surveillance study and sheds light on possible subtle changes following long-term exposure to copper-containing dust. Abstract : Objective: The aim of the study was to assess the effect of exposure to copper-containing dust on lung function and inflammatory endpoints among workers of a German copper plant, effects rarely studied before. Methods: One hundred four copper-exposed smelter workers and 70 referent workers from the precious metal and lead facilities were included, with different metal exposures in both groups due to the different process materials. Body plethysmography, exhaled nitric oxide (FeNO) measurements, and blood sampling were conducted in all workers. Smoking status and the use of respiratory protective equipment were considered. In a subgroup of 40 nonsmoking volunteers (28 copper-exposed and 12 referents), sputum biomarkers were assessed. Results: Median lung function values of both copper-exposed and the referent groups were within reference ranges of "healthy" individuals, and statistical differences between the groups were mostly not evident. Similarly, differences in blood and sputum biomarkers were too small to be biologically relevant. Conclusion: The results suggest the absence of the detectable effects of copper-containing dust exposure on lung function or chronic inflammation within the investigated cohort.